Barriers and facilitators for healthcare providers to implement family-centered care in Parkinson's disease: a scoping review - Sun, Wen-Jing; Peng, Ye-Jie; Liang, Yan (Frontiers in Neurology, 2023)
Aims This study aimed to identify and synthesize the barriers and facilitators to the implementation of family-centered care in Parkinson's disease (PD) and to provide a reference for evidence-based Parkinson's disease nursing practice. Methods This scoping review follows the methodology framework proposed by Arksey and O'Malley. Four databases including PubMed, Web of Science, Embase, and Cochrane Library were searched. Barriers and facilitators were summarized based on the ecological family-centered model. Results Through a comprehensive literature search, 35 studies were found for this scoping review. Barriers and facilitators to implementing family-centered care in PD included physiological factors, environmental factors, culturally based conflicts, living arrangements, education or skills training, group experiences, and individual and family consultations. Conclusion Implementing family-centered care in Parkinson's disease is essential to providing comprehensive care that improves outcomes for both PD patients and their family members.